Separation of iron and zinc from manganese nodule leach liquor using TBP as extractant. (1st September 2013) - Patnaik, P.; Baba, A. A.; Nathsarma, K. C.; Sarangi*, K.; Subbaiah, T.
Abstract : In this work, the separation of total Fe and Zn leading to the purification of Mn from manganese nodule leach liquor were carried out from hydrochloric acid solution by tributylphosphate with methyl iso-butyl ketone (phase modifier) dissolved in kerosene. The simulated solution comprised of 0·29 mol L −1 Mn, 0·12 mol L −1 Fe, 0·087 mol L −1 Zn and 2·3 mol L −1 HCl was used for the study. Different parameters such as extractant and acid concentrations affecting the optimum extraction condition for the investigated metal ions were examined. The McCabe-Thiele plots for extraction and stripping were constructed and scrubbing studies were carried out. Total Fe was first separated and co-extracted Zn in the loaded organic was removed by scrubbing with ferric chloride solution; and the remaining Zn was then removed by tributylphosphate. Finally, extraction of 100%Fe and 99·7%Zn; and about 99·5% stripping efficiencies in both the cases were achieved.